2021
DOI: 10.1002/jaba.807
|View full text |Cite
|
Sign up to set email alerts
|

Stability of preference and reinforcing efficacy of edible, leisure, and social attention stimuli

Abstract: Behavior analysts have developed an extensive technology of assessing preferences, but little research has evaluated the extent to which preferences change over time. In this study, monthly paired-stimulus edible, leisure, and social preference assessments and bimonthly reinforcer assessments were conducted over a 1-year period with 4 individuals with developmental disabilities. Across participants, short-term (i.e., month to month) preference was most stable for edible items (average Spearman rank-order corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Additionally, assessments conducted with social interaction stimuli resulted in higher correlation coefficients than those conducted with leisure items. Although pre-session levels of satiation and deprivation may have influenced these results, another potential mediator of preference stability as suggested by Butler and Graff (2021) and Fahmie et al (2015) might be that edibles are primary reinforcers and as such, preference for this type of stimulus may be more stable over time compared to conditioned reinforcers (i.e., leisure items; social stimuli). Specifically, Butler and Graff (2021) found that preference was most stable for edible items, followed by leisure items, and then social stimuli.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, assessments conducted with social interaction stimuli resulted in higher correlation coefficients than those conducted with leisure items. Although pre-session levels of satiation and deprivation may have influenced these results, another potential mediator of preference stability as suggested by Butler and Graff (2021) and Fahmie et al (2015) might be that edibles are primary reinforcers and as such, preference for this type of stimulus may be more stable over time compared to conditioned reinforcers (i.e., leisure items; social stimuli). Specifically, Butler and Graff (2021) found that preference was most stable for edible items, followed by leisure items, and then social stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, edible items have been shown to maintain responding over longer periods of time compared to leisure items (Fahmie et al, 2015) and as such, may be more likely to produce consistent preference assessment outcomes across repeated administrations. Additionally, preference for edibles may remain more stable over time because they are primary reinforcers (Butler & Graff, 2021;Fahmie et al, 2015). Taken together, changes in preference assessment outcomes occur for a variety of reasons and may be desirable in some cases (e.g., an individual may have item rigidity or restrictions and you want preference to shift); however, it is always important to capture stimuli that are truly preferred and function as reinforcers when developing treatment programs.…”
Section: Introductionmentioning
confidence: 99%
“…Although participant characteristics were not controlled (e.g., age, communication repertoire, severity of ASD symptomology) and typically developing children were not included, the current study provides evidence that social interactions were reinforcing for 9 out of 21 participants (42.8%). This finding, along with results from preference and reinforcer assessments of social interaction (Butler & Graff, 2021;Clay et al, 2013;Clay et al, 2018;Davis et al, 2017;Davis et al, 2021;Goldberg et al, 2017;Huntington & Higbee, 2018;Kelly et al, 2014;Lang et al, 2014;Morris & Vollmer, 2019, 2020a, 2020b, 2020c, 2020dNuernberger et al, 2012;Piazza et al, 1999;Smaby et al, 2007;Wolfe et al, 2018), bring into question the assumption that social interactions are not reinforcing for individuals with ASD. Nevertheless, additional research is needed to elucidate factors influencing the function of social interaction with individuals with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic stimulus preference assessments (SPAs) have been used to identify preferred stimuli (e.g., edibles and toys) and activities that can be used as reinforcers in intervention programs for individuals with (Tullis et al, 2011) and without (Cote et al, 2007; Resetar & Noell, 2008) intellectual and developmental disabilities (IDD). Preferred stimuli are typically those an individual selects or interacts with most in an SPA, and it is hypothesized that the most preferred stimuli are likely to be the most potent reinforcers (e.g., Butler & Graff, 2021; Pace et al, 1985). Various SPAs have been used to identify preferred stimuli and activities (see Hagopian et al, 2004 and Saini et al, 2021 for a review of SPAs) and generally involve presenting one or more stimuli to an individual and measuring some response (e.g., selection response or interaction with stimuli).…”
mentioning
confidence: 99%
“…Although previous research has suggested the utility of SPAs for identifying reinforcers, there are numerous variables that may influence the outcomes of SPAs. These variables include history effects, such as the time that elapses between assessments (Butler & Graff, 2021; Hanley et al, 2006; Zhou et al, 2001) and motivating operations, such as programmed periods of satiation and deprivation of particular stimuli (Gottschalk et al, 2000; McAdam et al, 2005; Vollmer & Iwata, 1991). Additionally, the arrangement or modality of the assessment may influence results.…”
mentioning
confidence: 99%